Visible and hidden costs of human-elephant conflict on smallholders in Peninsular Malaysia - Sinha, Sinchita (2022)
Human-elephant conflict (HEC) is an ongoing issue of concern in all elephant range countries including Peninsular Malaysia. The clearing of forest land for agricultural expansion and urbanisation has reduced available habitat for elephants and other wildlife. The competition for space, that results in forest further fragmentation, leads to conflict which adversely affects communities living next to forest with elephants. Since smallholder community’s land represents about 38% in total planted area of oil palm and 93% of the planted rubber area in Malaysia, understanding the impact of human-elephant conflict on them is crucial when designing HEC mitigation approaches and in promoting human-elephant coexistence for the agriculture sector. The smallholder community in Malaysia is categorised into two groups, namely: i) Independent smallholders – those who grow their crops without help from external agencies and ii) Organised smallholders – farmers who are supported by government or any organization either through technical assistance, finance, or agricultural inputs. Following a participatory research approach, and a snowball sampling technique I assessed the Visible cost (e.g., either monetary or by considering the cost of seedlings, fertilizers, and pesticides) and Hidden cost (e.g., worry and exhaustion from guarding crops, loss of work opportunities, etc) for both independent (n=142) and organised (n=27) smallholders and examined their perception of insurance schemes as a financial tool. Respondents perceived elephants, wild boars, and macaques as top conflict animals. Yearly crop loss suffered by 137 respondents on oil palm, rubber, durian, and banana that included seedling, labour, fertilizer, and pesticide cost, due to conflict with elephants, was reported to be RM 2,962,475 for an area size of 11,460.51 acres. Mitigation cost (covering 5 years) that included installation of measures and repair cost amounted to RM 3,593,449.32 as reported by the smallholders during the survey. The smallholders admitted that factors such as lack of knowledge (58%), high cost (82%), and failed past attempts (66%) prevented them from deploying mitigation methods. But they were willing to try insurance as a financial mitigation tool to secure their crops against damage. In all, 35.5% (60) smallholders were willing to invest in insurance premium with majority opting for an amount below RM 200, which reflects the range they are willing to invest monetarily. Aspects of hidden cost that comprised of psychological stress (92.47%), fatigue due to guarding crops (84.56%) in the night and being vigilant (89.47%) were also reported. Opportunity loss was reported to be lower than expected. Attitudes of smallholders were found to be influenced by age, level of education, and past experience of property damage. These results can help support management recommendations to promote human-elephant coexistence for the agriculture sector in Peninsular Malaysia, such as the development of smallholder insurance scheme and helping conservation agencies understand grievances and challenges faced by smallholders in implementing conflict mitigation measures.